2012
DOI: 10.2109/jcersj2.120.25
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of particulate InN crystal by the reaction of InCl3 with LiNH2

Abstract: A method to synthesize indium nitride (InN) crystal by the reaction of InCl 3 with LiNH 2 under N 2 atmosphere was studied. InN was formed at the temperature ranging from 350 to 450°C under 0.1 MPa N 2 atmosphere. X-ray diffraction (XRD) pattern and transmission electron microscope (TEM) image indicated that synthesized InN was crystalline powder with a wurtzite structure. Band gap was determined by plotting (¡h¯) 2 vs. h¯for direct transition and the value of 0.83 eV was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Particulate InN crystals with a diameter of approximately 800 nm were obtained. 25 These studies have demonstrated the effect of raw materials (In 2 O 3 and LiNH 2 ) on the morphology of InN crystals. However, none of the above-mentioned studies have investigated the morphology control of InN particles at the nanoscale and their photoelectrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particulate InN crystals with a diameter of approximately 800 nm were obtained. 25 These studies have demonstrated the effect of raw materials (In 2 O 3 and LiNH 2 ) on the morphology of InN crystals. However, none of the above-mentioned studies have investigated the morphology control of InN particles at the nanoscale and their photoelectrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…26 Based on the results, we anticipated that InN nanocrystals could be synthesized using LiClcontaining molten salts. In this paper, we use a KCl-LiCl mixture with eutectic composition of 60% mol LiCl and 40% mol KCl that has a melting point of 353 C (as shown in Table S1 † 28 ), taking into consideration that the molten salts for nitridation reactions of InN should have a melting point that is lower than the synthesis temperature at 400-500 C. 25,29 Herein, we present, for the rst time, the effect of molten salt on the nitridation synthesis of single-phase InN nanocrystals. The InN nanocrystals were successfully obtained at relatively low temperatures ranging from 400 C to 500 C. In addition, the photoelectrochemical cell fabricated using the InN electrodes exhibited a photocurrent response under visible and near-IR light irradiation.…”
Section: Introductionmentioning
confidence: 99%